Przyczyny fałszywie dodatniego rozpoznania jaskry - Szaflik, Jerzy; Zaleska-Żmijewska, Anna; Jędruch, Anna; Liberek-Grabska, Iwona (Klinika Oczna / Acta Ophthalmologica Polonica Supplement, 2004)
Glaucoma, if left untreated, leads to blindness, but if detected early, disease progression can be stopped or slowed with drugs or surgical treatment. The development of existing and new diagnostic methods has allowed substantial improvement in the clinical detection of possible glaucoma. But in some cases false positive diagnoses can be undertaken. In this paper we discussed reasons for the wrong evaluation of factors suggesting the diagnosis of glaucoma, with special interest for mistakes in applanation tonometry results caused by thick cornea.